Effects of focused continuous pulsed electromagnetic field therapy on early tendon-to-bone healing: rat supraspinatus detachment and repair model. Issue 5 (1st May 2021) - Dolkart, Oleg; Kazum, Efi; Rosenthal, Yoav; Sher, Osnat; Morag, Guy; Yakobson, Elad; Chechik, Ofir; Maman, Eran
Abstract : Aims: Rotator cuff (RC) tears are common musculoskeletal injuries which often require surgical intervention. Noninvasive pulsed electromagnetic field (PEMF) devices have been approved for treatment of long-bone fracture nonunions and as an adjunct to lumbar and cervical spine fusion surgery. This study aimed to assess the effect of continuous PEMF on postoperative RC healing in a rat RC repair model. Methods: A total of 30 Wistar rats underwent acute bilateral supraspinatus tear and repair. A miniaturized electromagnetic device (MED) was implanted at the right shoulder and generated focused PEMF therapy. The animals' left shoulders served as controls. Biomechanical, histological, and bone properties were assessed at three and six weeks. Results: Extension of the tendon from preload to the maximum load to failure was significantly better in the PEMF-treated shoulders at three weeks compared to controls (p = 0.038). The percentage strain was significantly higher in the PEMF group at both timepoints (p = 0.037). Collagen organization was significantly better (p = 0.034) as was tissue mineral density in the PEMF-treated group at three weeks (p = 0.028). Tendon immunohistochemistry revealed a prominent increase in type I collagen at the repair site at three weeks following continuous PEMF treatment compared with controls. None of the other tested parameters differed between the groups. Conclusion: MED-generated PEMF may enhance early postoperative tendon-to-bone healing in an acute rat supraspinatus detachment and repair model. Superior biomechanical elasticity parameters together with better collagen organization suggest improved RC healing. Cite this article: Bone Joint Res 2021;10(5):298–306.